Gifted Conversations: Discursive Patterns in Gifted Classes. (April 2014) - Netz, Hadar
Despite the attested association between giftedness and high verbal abilities, and despite the central role attributed to classroom discourse analysis in educational research, discourse in gifted classes has not received due scholarly attention. This study takes a first step toward filling this gap. This study offers a microanalysis of a corpus of recorded and transcribed interactions from classes of gifted students in the Commonwealth of Virginia. This study focuses on student initiations and on the ways teachers handle these initiations. It is argued that the preponderance of student initiations in the classes observed sets a fertile ground for dialogic discourse to develop. However, student initiations do not guarantee the emergence of dialogic discourse, since teachers sometimes employ instructional practices that hinder its emergence.